Satisfaction regarding the methods used to evaluate hotel performance - Machado, M. J. C. V. (2018)
This study has four specific objectives: to analyse the association between hotel features and the methods used to evaluate hotel performance; to analyse the convergence between what the theory considers as appropriate performance evaluation methods, and the opinion of the hotels’ financial managers; to identify the factors that explain why the same method is considered appropriate in some hotels and not in others; to analyse whether there is an association between the method used to evaluate hotel performance and customer satisfaction. Data collection was made using two sequential methods. Firstly, we conducted a survey directed at the financial managers of 3, 4 and 5-star hotels located in Portugal, where we obtained 189 completed surveys. Secondly, we collected information regarding the degree of customer satisfaction for the hotels responding to the initial survey using the information available on the online platform Tripadvisor.com. The results obtained allow us to indicate as main contributions the following: validation of the expectations confirmation paradigm as an adequate theoretical model to explain customer satisfaction in hotels, namely showing that the performance evaluation methods can be regarded as factors affecting the actual customer experience; to demonstrate that the satisfaction indicator room is what contributes the most to the level of overall customer satisfaction; to demonstrate the existing convergence between what the theory considers as appropriate performance evaluation methods, and the opinion of the hotels’ financial managers, unlike what was previously reported in other industries.